The potential for bioenergy crops to contribute to meeting GB heat and electricity demands. Issue 2 (31st October 2013) - Wang, Shifeng; Hastings, Astley; Wang, Sicong; Sunnenberg, Gilla; Tallis, Matthew J.; Casella, Eric; Taylor, Simon; Alexander, Peter; Cisowska, Iwona; Lovett, Andrew; Taylor, Gail; Firth, Steven; et al.
Abstract The paper presents a model system, which consists of a partial equilibrium model and process‐based terrestrial biogeochemistry models, to determine the optimal distributions of both Miscanthus (Miscanthus × giganteus) and short rotation coppice willow (SRC) (Salix. viminalis L. x S. viminalis var Joruun) in Great Britain (GB), as well as their potential contribution to meet heat and electricity demand in GB. Results show that the potential contribution of Miscanthus and SRC to heat and electricity demand is significant. Without considering farm‐scale economic constraints, Miscanthus and SRC could generate, in an economically competitive way compared with other energy generation costs, 224 800 GWh yr−1 heat and 112 500 GWh yr−1 electricity, with 8 Mha of available land under Miscanthus and SRC, accounting for 66% of total heat demand and 62% of total electricity demand respectively. Given the pattern of heat and electricity demand, and the relative yields of Miscanthus and SRC in different parts of GB, Miscanthus is mainly favoured in the Midlands and areas in the South of GB, whereas SRC is favoured in Scotland, the Midlands and areas in the South of GB.